Understanding MSMEs’ Resistance to QRIS Adoption: The Role of Perceived Usefulness and Social Influence in a Standardized Digital Payment System - David Limanta; Dhyah Harjanti (Jurnal Riset Ekonomi, Manajemen, dan Bisnis, 2026)
The rapid growth of digital payment systems has encouraged the use of QRIS in Indonesia, yet its adoption among micro and small enterprises (MSMEs) remains uneven. Many MSMEs still choose not to use QRIS in their daily transactions. This study aims to examine the factors that drive this resistance by focusing on perceived lack of usefulness, perceived difficulty of use, resource factors, technology anxiety, and social influence. In addition, the study explores the mediating role of perceived lack of usefulness in shaping resistance behavior. Data were collected from 204 MSMEs in Surabaya who have not adopted QRIS and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that perceived lack of usefulness and social influence significantly influence resistance to QRIS adoption. In contrast, perceived difficulty of use, resource factors, and technology anxiety do not have a significant effect. Furthermore, perceived lack of usefulness is found to mediate the relationship between social influence and resistance. These findings indicate that MSMEs’ resistance is driven more by how they perceive the benefits of QRIS and by their social environment than by technical limitations. This suggests that efforts to increase adoption should focus not only on improving technical accessibility but also on strengthening perceived value and peer influence.